PERANALYSIS OF ACADEMIC WEBSITE USING WEBQUAL 4.0 METHOD AND IMPORTANCE-PERFORMANCE ANALYSIS (IPA) - Andrean, Fizal Okta; Megawati; Fronita, Mona; Saputra, Eki (Jurnal Teknik Informatika (Jutif), 2024)
The Academic Website plays a crucial role as the primary channel for delivering academic information to the entire academic community. Its main functions include providing vital information such as Graduation Schedules, Academic Year Calendars, and Scholarship Announcements, making it an indispensable source of information for students. The quality of services on this website is a crucial aspect in meeting the information needs of students. This research aims to evaluate and enhance the quality of the website, with a primary focus on improving services for students and achieving a higher ranking in Webometrics State Islamic Religious Higher Education Institution (PTKIN), currently positioned at 18th. The research methodology utilizes WebQual 4.0 to assess the website's quality, focusing on usability, information quality, and service interaction quality. The Importance-Performance Analysis (IPA) approach is employed to guide the website's development based on the importance and actual performance of each quality attribute. The Webqual Index analysis results indicate that the website achieves a score of 0.85 or 85%, highlighting good service quality but also indicating the need for improvement in information and service interaction quality. This study produces a comprehensive guide for the necessary changes and developments in the Academic Website. The guide ensures that the website aligns with the dynamic needs of the university community, creating a virtual environment that supports and facilitates access to information for students. These improvements are expected not only to enhance the Webometrics PTKIN ranking but also to increase student satisfaction and engagement in the academic process